Gambaran kesehatan kerja pekerja bangunan di Kota Denpasar periode Agustus-Oktober 2017 - Faiz Afano; Putu Cintya Denny Yuliatni; Luh Seri Ani (Intisari Sains Medis, 2020)
Background: Building construction is one of the most significant sectors related to the economic development in a country. However, the development of construction sector in Indonesia also has an impact in increasing problem regarding the occupational diseases, particularly among construction workers. In addition, construction workers require health insurance to facilitate the access to the nearest health center.Aim: The study aimed to describe the complaints of disease and behavior of accessing health facilities among construction workers in Denpasar city.Methods: This is a descriptive with cross-sectional research design which was implemented in Denpasar city among 101 subjects. The primary data was in the form of interview using questionnaire.Results: The result revealed that all subjects were male. Majorities were ≤30 years old, came from outside Bali, had worked for ≤5 years, with duration of work ≤8 hours, and in the light worker group. The construction workers mostly complained about lower back pain (34.4%). A total of 63.4% of construction workers do not have health insurance, especially for workers who came from outside Bali.Conclusion: Lower back pain tends to occur in workers from age group of  >30 years, workers who work for ≤5 years, workers with duration of work >8 hours, and in the heavy worker group. The tendency of ownership of health insurance in construction workers is not based on the length of work and the job field.  Latar belakang: Konstruksi bangunan merupakan salah satu sektor yang sangat penting dalam perkembangan perekonomian suatu negara. Seiring dengan berkembangnya sektor pembangunan di Indonesia berdampak pula pada peningkatan masalah penyakit akibat kerja terutama pada pekerja bangunan. Selain itu pekerja bangunan memerlukan adanya jaminan kesehatan berupa asuransi untuk memudahkan akses ke fasilitas kesehatan terdekat.Tujuan: Tujuan penelitian ini adalah untuk mengetahui gambaran keluhan penyakit dan perilaku mengakses fasilitas kesehatan pada pekerja bangunan di Kota Denpasar.Metode: Jenis penelitian ini adalah deskriptif dengan pendekatan cross-sectional yang dilaksanakan di di Kota Denpasar dengan total responden 101 orang. Penelitian ini menggunakan data primer berupa hasil wawancara menggunakan kuisioner.Hasil: Dalam penelitian ini didapatkan hasil bahwa semua subyek penelitian adalah laki-laki. Mayoritas berusia ≤30 tahun, berasal dari luar Bali, telah bekerja ≤5 tahun, dengan durasi bekerja ≤8 jam, dan bidang pekerjaan ringan.  Keluhan yang paling banyak adalah nyeri punggung bawah (34.4%). Sebanyak 63.4% pekerja bangunan tidak memiliki asuransi kesehatan, terutama bagi pekerja yang berasal dari luar Bali.Kesimpulan: Nyeri punggung bawah cenderung terjadi pada usia pekerja > 30 tahun, pekerja yang bekerja selama ≤5 tahun, pekerja dengan durasi kerja > 8 jam, dan pada kelompok pekerja berat. Kecenderungan kepemilikan asuransi kesehatan pada pekerja bangunan tidak berdasarkan lama bekerja dan bidang pekerjaan.